Poverty and Inequality Changes in Turkey (2003-2006) - Aran, Meltum; Demir, Sirma; Sarica, Özlem; Yazici, Hakan (World Bank, Ankara, 2017)
Poverty in Turkey has declined significantly between 2003 and 2006, as a result of rapid poverty reduction in urban areas. In the same time period, the reduction in poverty in rural areas has been slow or non-existent. As a result, the relative risk of poverty has increased in this time period for those employed in agricultural sector, living in rural areas and in large households. Inequality in urban areas has decreased as a result of high growth in the consumption levels of the urban poor compared to richer deciles, while no significant changes to inequality measures have been noted in rural areas. In fact, the consumption levels of poorest groups in rural Turkey have declined between 2003 and 2006. Child poverty has also been persistent in this time period, with the relative risk of poverty for children (ages0-19) increasing over time.